2023
DOI: 10.1021/acs.jpcc.2c08117
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Relevance of Surface Reactions and Lattice Diffusion in the Dynamics of Ce–Zr Oxides Reduction–Oxidation Cycles

Abstract: Reduction–oxidation cycles in oxides are ubiquitous in oxygen storage and transport, chemical looping processes, and fuel cells. O-atom addition and removal are mediated by coupling reactions of oxidants and reductants at surfaces with diffusion of O-atoms within oxide crystals, with either or both processes as limiting steps. CeO2–ZrO2 solid solutions (CZO) are ubiquitous in practice. They are used here to illustrate general experimental strategies and reaction–diffusion formalisms for nonideal systems that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…In a similar chemical looping system to the SrFeO 3−δ materials impregnated with Ag investigated here, Hwang et al found that for reduction and oxidation of Ce 0.5 Zr 0.5 O 2−δ impregnated with Pt, the presence of Pt enhanced the rate of oxygen release but had no effect on the rate of oxygen uptake. Hence, the authors concluded that the rate of reduction of Pt/Ce 0.5 Zr 0.5 O 2−δ was limited by the surface reaction, i.e., formation of O 2 molecules from O 2– ions, whereas oxidation was limited by O 2– diffusion.…”
Section: Discussionmentioning
confidence: 71%
“…In a similar chemical looping system to the SrFeO 3−δ materials impregnated with Ag investigated here, Hwang et al found that for reduction and oxidation of Ce 0.5 Zr 0.5 O 2−δ impregnated with Pt, the presence of Pt enhanced the rate of oxygen release but had no effect on the rate of oxygen uptake. Hence, the authors concluded that the rate of reduction of Pt/Ce 0.5 Zr 0.5 O 2−δ was limited by the surface reaction, i.e., formation of O 2 molecules from O 2– ions, whereas oxidation was limited by O 2– diffusion.…”
Section: Discussionmentioning
confidence: 71%
“…Recently, Hwang et al 58 defined a Thiele modulus relating the volumetric CO oxidation rate on ceria-zirconia (CZO) surfaces to the volumetric diffusion rate of O atoms at the CZO surface. A Thiele modulus much less than unity implies that oxygen diffusion is fast relative to the surface reaction to an extent that the surface reduction rate will not be limited by diffusion of O atoms to the surface.…”
Section: Kinetics Of Hydrogen Combustion Half-cyclesmentioning
confidence: 99%